Analysis of the Strength of Timber and Glulam Timber Beams with Steel Reinforcement - Usman, Arie Putra; Sugiri, Saptahari (Journal of Engineering and Technological Sciences, 2015)
Indonesia is a tropical country with abundant tropical timber that can be used as a building material. Wood is a renewable material, thus making it an environmentally friendly construction material. However, the dimensional limitations of solid wood may pose problems in structural constructions. Wood material also has some disadvantages, such as brittle failure. However, the ductility of wood can be increased because of plasticity occurring in the compression zone. Wood material with good ductility can be obtained by reinforcing it in the tensile zone. This study is about the strength of wood material for use as a material for structural elements. Based on the analytical findings, the bending capacity of wood can be improved by adding reinforcements to the tensile zone.